Daidzin improves the cisplatin chemosensitivity for osteosarcoma via binding to β-catenin protein and suppressing the wnt pathway - Peng Wang; Hao Lu; Chi Zhang; Renwei Wang; Xiaobo Chen; Lixin Qiao; Zhiyong Wang; Wenge Wang (Scientific Reports, 2025)
Abstract Osteosarcoma (OS) mainly occurs in adolescents and children, accompanied with chemotherapy resistance as well as unsatisfactory treatment outcome. Recent studies have discovered a series of natural products with anticancer activity, which have important translational value. Daidzin has been reported with a variety of biological activities. We aim to explore whether daidzin has therapeutic potential for OS. In this study, cell based and in vivo studies showed that daidzin can inhibit the ability of OS cells to proliferate and metastasize. Compared to single treatment arms, combined treatment of daidzin and cisplatin, a classic recommendation for OS treatment, showed a further suppression in OS cell viability, migration and invasion ability, and led to further apoptosis. Mechanistically, daidzin was found to downregulate the β-catenin expression and further inhibited the Wnt pathway. However, daidzin did not alter the transcriptional level of β-catenin. Molecular docking showed a potential interaction between daidzin and β-catenin protein, and their combination was further confirmed by thermal shift assay and MST assay. Daidzin was found to reduced protein stability of β-catenin, and only transfection of β-catenin mutant (a mutant that targets the binding sites to daidzin) at the same time as daidzin treatment could effectively attenuate the antitumor effect of daidzin. Our study suggests that daidzin has translational value as a potential adjuvant to improve treatment outcomes for OS.